MIHAYLO ROUDNITSCIY NOT FAR FROM - Sevrasevych М. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
Mihaylo Roudnitsky. "From Peaceful to Waving. Between an idea and form. What «Young Muse»? - Drogobich: Publishing firm of «Revival», 2009. - 502 p. - (Series «Cogito: educational the classics)".